2014
DOI: 10.1038/npp.2014.118
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BDNF Signaling in D1R-Expressing NAc Neurons Enhances Morphine Reward by Reducing GABA Inhibition

Abstract: The nucleus accumbens (NAc) has a central role in the mechanism of action of drugs of abuse. The major neuronal type within the NAc is the GABAergic medium spiny neuron (MSN), with two major subpopulations defined-termed D1-type and D2-type MSNs-based on the predominant dopamine receptor expressed. However, very little is known about the contribution of altered GABAergic function in NAc MSNs to the neural and behavioral plasticity that contributes to the lasting actions of drugs of abuse. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 38 publications
10
72
3
Order By: Relevance
“…We also noted that several glutamate receptor subunits (Gria4, Grin2d, Grin3a) were upregulated by interrupted morphine, but only in comparison to control in the nucleus accumbens. These changes are consistent with plasticity of excitatory and inhibitory synaptic transmission caused by intermittent morphine exposure (50)(51)(52).…”
Section: Genes and Pathways Regulated By Interrupted Morphine Exposuresupporting
confidence: 81%
“…We also noted that several glutamate receptor subunits (Gria4, Grin2d, Grin3a) were upregulated by interrupted morphine, but only in comparison to control in the nucleus accumbens. These changes are consistent with plasticity of excitatory and inhibitory synaptic transmission caused by intermittent morphine exposure (50)(51)(52).…”
Section: Genes and Pathways Regulated By Interrupted Morphine Exposuresupporting
confidence: 81%
“…Koo et al (2014) have also observed a negative relationship between accumbens BDNF and morphine CPP memory, but in a cell-type specific manner. That is, selective ablation of the TrkB BDNF receptor on dopamine D1 receptor-containing medium spiny neurons resulted in reduced GABA-A receptor currents in these neurons, ultimately promoting morphine reward (Koo et al, 2014). Given that morphine exposure led to a similar cell-type specific downregulation of TrkB in D1-neurons, the authors hypothesized that this neuroadaptation contributes to morphine addiction.…”
Section: Bdnf and Opiate Seekingmentioning
confidence: 82%
“…Similarly, optical activation of NAc D1-, but not D2-MSNs enhances morphine CPP (Koo et al, 2014). Indeed, recent evidence reveals expression of μ-opioid receptors within NAc D1-MSNs of the direct pathway to be necessary to support opiate-induced CPP and locomotor sensitization (Cui et al, 2014).…”
Section: Discussionmentioning
confidence: 99%